2014
DOI: 10.5152/tjbh.2014.1778
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer and Posttraumatic Growth

Abstract: The current methods for early diagnosis and increased treatment options have improved survival rates in breast cancer. Breast cancer diagnosis effects individuals in physical, psychological and social dimensions either positively or negatively. In the literature, usually the negative effects encountered in the period after the diagnosis of breast cancer are mostly described, with limited data on the positive effects. Nevertheless, the identification of positive changes and defining its determinants is importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…The average age of the participants and period after diagnosis were 47.63 (SD, 9.33) years and 5.92 (SD, 5.56) months. The mean ECW and ICW scores of the women were 31.78 (SD, 4.73) and 16.87 (SD, 4.04), and the total score of the MSPSS was 73.21 (SD, 11.31).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average age of the participants and period after diagnosis were 47.63 (SD, 9.33) years and 5.92 (SD, 5.56) months. The mean ECW and ICW scores of the women were 31.78 (SD, 4.73) and 16.87 (SD, 4.04), and the total score of the MSPSS was 73.21 (SD, 11.31).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the social support provided to women with breast cancer has a major effect in coping with stress . Social support enables women to gain a positive point of view on their medical condition and cope with their disease better, and it also increases the effectiveness of treatment . It is revealed in the literature that social support is useful for patients' ability to cope with stress, to physically and psychologically adapt, and have enhanced quality of life .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following factors are thought to determine the occurrence of PTG: personality factors, the specifics of the stressful situation, support, emotions, behaviors related to dealing with the disease, and strategies of coping with stress. 4,5 It can be considered whether patients' susceptibility to changes in BI could be another variable that may influence the occurrence of PTG. Therefore, this paper and further research could be important in contributing to the support of oncological patients in this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudos realizados com sobreviventes de câncer de mama identificaram vários fatores que influenciam o crescimento pós-traumático, dentre eles: fatores pessoais (relacionamentos pessoais, confiança nos profissionais, características demográficas e outros); fatores relacionados a eventos (características clínicas, estadiamento da doença, e outros); fatores ambientais (apoio social da família, dos amigos, do companheiro, contato com outros sobreviventes de câncer, satisfação no relacionamento familiar e conjugal); desequilíbrio entre câncer e a percepção de si mesma e do mundo; atitudes; comportamentos; emoções; estratégias de enfrentamento (espiritualidade, meditação reflexiva, pensamento positivo, processos cognitivos, resiliência). Elevados níveis de crescimento pós-traumático amenizam a depressão e o estresse e estão relacionados com a qualidade de vida (MOLS et al, 2009; LELORAIN; BONNAUD-ANGIGNAC; FLORIN, 2010;FALLAH et al, 2012;BRIX et al, 2013;INAN;USTUN, 2014 Assim, esse sobrepeso nos serviços de saúde brasileiros pode refletir na amplitude da resolutividade do cuidado, levando também os brasileiros, como no caso das mulheres com câncer de mama, a procurar atendimento para seus agravos de saúde do outro lado da fronteira, mesmo sem a garantia da continuidade da atenção.…”
Section: Conectando Os Atributos Da Atenção Primária à Saúde à Teoriaunclassified